Thin Film Condensation on Nanostructured Surfaces. (15th February 2018) - Oh, Junho; Zhang, Runyu; Shetty, Pralav P.; Krogstad, Jessica A.; Braun, Paul V.; Miljkovic, Nenad
Abstract: Water vapor condensation is a ubiquitous process in nature and industry. Over the past century, methods achieving dropwise condensation using a thin (<1 µm) hydrophobic "promoter" layer have been developed, which increases the condensation heat transfer by ten times compared to filmwise condensation. Unfortunately, implementations of dropwise condensation have been limited due to poor durability of the promoter coatings. Here, thin‐film condensation which utilizes a promoter layer not as a condensation surface, but rather to confine the condensate within a porous biphilic nanostructure, nickel inverse opals (NIO) with a thin (<20 nm) hydrophobic top layer of decomposed polyimide is developed. Filmwise condensation confined to thicknesses <10 µm is demonstrated. To test the stability of thin‐film condensation, condensation experiments are performed to show that at higher supersaturations droplets coalescing on top of the hydrophobic layer are absorbed into the superhydrophilic layer through coalescence‐induced transitions. Through detailed thermal‐hydrodynamic modeling, it is shown that thin‐film condensation has the potential to achieve heat transfer coefficients approaching ≈100 kW m −2 while avoiding durability issues by significantly reducing nucleation on the hydrophobic surface. The work presented here develops an approach to potentially ensure durable and high‐performance condensation comparable to dropwise condensation. Abstract : Thin‐film condensation on hydrophobic‐coated nickel inverse opal structures enables heat transfer performance approaching that of dropwise condensation while achieving higher robustness by confining the condensate film and reducing nucleation on the hydrophobic layer.